Studi keseimbangan air di sub sws Cimanuk - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Psikologi Universitas Gadjah Mada, 1998)
ABSTRACT Cimanuk area stretches along the north coastline of Java (in the east part of West Java) and lies within the Province of West Java. The area covers the Kabupatens of Cirebon, Majalengka, Sumedang, Indramayu, Garut and Bandung. The area has been developed as irrigation (about 187,000 ha), residential and industry areas.The present population is estimated about 4,46 millions of which 49% live in urban area. The population of the area is predicted to reach 5,4 millions in the year of 2020. These conditions induce the increase in the water demand, while the water availability is constant or decrease. The study of water balance consist of the calculation of the water availibility and of the water demand. The study area is divided into smaller units, called water districts. The water supply and demand situation in these water districts will be analysed. The study considers two reservoirs proposed in the water resources development master plan (SMEC, 1995), that are Jatigede dam (in the year of 2005) and Cipasang dam (in 2010). The results of the study show that in the existing condition, all of the water districts are deficit of water about 2.15 billion m3/year. After construction of Jatigede dam in 2005 the deficit of water will be about 528 million m3/year